2017
DOI: 10.1109/lcsys.2017.2718840
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Nodes Symmetries to Control Synchronization and Consensus Patterns in Multiagent Systems

Abstract: We present new conditions to obtain synchronization and consensus patterns in complex network systems. The key idea is to exploit symmetries of the nodes' vector fields to induce a desired synchronization/consensus pattern, where nodes are clustered in different groups each converging towards a different synchronized evolution. We show that the new conditions we present offer a systematic methodology to design a distributed network controller able to drive a network of interest towards a desired synchronizatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The aim of controlling cluster synchronization is to induce a synchronization regime where the networked system splits in groups of nodes, also called clusters, such that all the nodes in a cluster are synchronized, while different clusters exhibit distinct dynamical behaviors. This goal is reached with techniques based on pinning control [18], intermittent pinning control [24], aperiodically intermittent pinning control [25], or exploiting the network symmetries [26], [27].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of controlling cluster synchronization is to induce a synchronization regime where the networked system splits in groups of nodes, also called clusters, such that all the nodes in a cluster are synchronized, while different clusters exhibit distinct dynamical behaviors. This goal is reached with techniques based on pinning control [18], intermittent pinning control [24], aperiodically intermittent pinning control [25], or exploiting the network symmetries [26], [27].…”
Section: Introductionmentioning
confidence: 99%
“…It is already known that the structural balance condition endows the network topology with symmetries and drives network dynamics towards a desired synchronization or polarization pattern [16]. In addition to symmetries of network topology, the authors of [31] have shown that the symmetries of the nodes' vector fields are also of key importance to attain the specific synchronization pattern in opinion dynamics with the generalized ODE model (1). The rationale behind the idea is to examine Γ-equivariance of the intrinsic node dynamics.…”
Section: Theoremmentioning
confidence: 99%
“…For structurally balanced networks, the opinion dynamics of LTI systems (4) is naturally Γ-equivariant thanks to the fact that π i I commutes with every system matrix F i where i ∈ V a . For more results on symmetries and equivariance in collective behavior analysis of networked systems, readers are referred to [31], [32]. Remark 5.…”
Section: Theoremmentioning
confidence: 99%
“…Early consensus works focus on MASs with very primitive individual agent dynamics (such as single integrators or double integrators) [5][6][7][8], where only the information exchange among agents determines time evolution of the networks. Starting from them, the MASs with finite-dimensional linear dynamics have enticed intensive attention from the control community, which are more general and include integrator dynamics as a special case [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%